Pendugaan Model Kurva Pertumbuhan Berat Badan Pada Sapi Aceh (Bos indicus) - Sumadi Sumadi; Tety Hartatik; Hendra Saumar; Widya Pintaka Bayu Putra (Jurnal Ilmu Dan Teknologi Peternakan Indonesia (JITPI) Indonesian Journal of Animal Science and Technology), 2018)
Growth traits represent mirroring of individual availability to present genetic potency and growth on parts of the body. Observation on growth rate was based on the changes in body weight (BW) by adding ages from birth (1 day of age) to maturity age (>1261 days) periods from 142 animals (98 males and 44 females). Information of the ages was obtained based on herd records from 2010 - 2013. Two growth curve models consisted of Richard and Weibull models were used in this study based on CurveExpert 1.4 computer program. Research results showed that both models have a similar coefficient of determination (R2 = 0.99 ), but the lowest standard error (SE) value reached in Richard model (2.45). The optimum growth rate was reached until the age of 18 months (Richard) and 20 months (Weibull) with an optimum weight of about 135 kg for both models. As a result, selection based on weight at 18 months (550 days) of age was important for selecting the best bull and heifer.